Presenting a Smart Sukuk Model for Islamic Microfinance Institutions in Bangladesh: Towards Achieving SDGs - Muhammad, Niaz Makhdum; Kassim, Salina; Mahadi, Nur Farhah Binti; Ali, Engku Rabiah Adawiyah Engku (EkBis: Jurnal Ekonomi dan Bisnis, 2024)
The Islamic bonds and debts, according to Islamic Shariah, are referred to as Sukuk, which provides cheaper and interest-free funding options for businesses and lower-risk bonds for individual investors. This study aims to present a novel fintech-based (Smart) SRI Sukuk model that can be useful for Islamic microfinance institutions (IMFIs) of Bangladesh in managing the source of funds. This study adopted a systematic literature review approach to assess the benefits of using Smart SRI Sukuk for IMFIs. In addition, 15 experts on Islamic finance were interviewed to determine the best possible ways to integrate technology into the SRI Sukuk model. The outcomes of this study have confirmed the effectiveness of using a blockchain and smart contract-based SRI Sukuk for managing the source funds of Islamic microfinance institutions in Bangladesh. The Smart SRI Sukuk can be immensely beneficial for IMFIs that always find it difficult to arrange the source funds and manage those in an efficient manner. This study also focuses on emancipating the poor from the vicious cycle of poverty through implementing Islamic microfinance system, and thus contributing to achieving the sustainable development goals (SDGs). Future researchers and experts in Islamic finance will also find the ideas presented in this research helpful.